2018
DOI: 10.1002/joc.5937
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation variability and its relation to climate anomalies in the Bolivian Altiplano

Abstract: Precipitation variability over the Bolivian Altiplano is strongly affected by local climate and temporal variation of large-scale atmospheric flow. Precipitation is the main water source for drinking water and agricultural production. For this reason, a better understanding of precipitation variability and its relation with climate phenomena can provide important information for forecasting of droughts and floods, disaster risk reduction, and improvement of water management. We present results of an analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 57 publications
2
35
0
1
Order By: Relevance
“…This finding is consistent with that of Canedo‐Rosso et al . (2019) who found a negative correlation between austral summer precipitation and ENSO for the Bolivian Altiplano during 1948–2015. Interestingly, this study also demonstrated a significant negative correlation (at low frequency) with other climate indices, such as the North Atlantic Oscillation (NAO), Antarctic Meridional Mode (AMM) and Atlantic Multidecadal Oscillation (AMO).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with that of Canedo‐Rosso et al . (2019) who found a negative correlation between austral summer precipitation and ENSO for the Bolivian Altiplano during 1948–2015. Interestingly, this study also demonstrated a significant negative correlation (at low frequency) with other climate indices, such as the North Atlantic Oscillation (NAO), Antarctic Meridional Mode (AMM) and Atlantic Multidecadal Oscillation (AMO).…”
Section: Resultsmentioning
confidence: 99%
“…Additional socioeconomic factors such as crowded settings or households with poor hygiene, sanitation, and contaminated water could exacerbate the propagation of EAEC during the cold-dry season. Studies with more recent EAEC prevalence data need to be considered to evaluate whether the biannual periodicity of EAEC remains univariable even after the severe consequences of climate change and water management that La Paz and Cochabamba cities experienced in the last decade (53).…”
Section: Discussionmentioning
confidence: 99%
“…In most parts of Bolivia, precipitation is the main water source for drinking water and agriculture. The Bolivian Altiplano, however, is strongly affected by local climate and a high degree of variation [13]. The precipitation gradient decreases to the south [14].…”
Section: A An Overviewmentioning
confidence: 99%